Factor inhibiting HIF can catalyse two asparaginyl-hydroxylations in VNVN motifs of ankyrin fold proteins - Leissing, TM; Hardy, AP; Chan, H; Wang, Y; Tumber, A; Chowdhury, R; Fang, P; Coleman, ML; Cockman, ME; Kramer, HB; Berridge, G; Fischer, R; et al. (Elsevier, 2022)
The aspariginyl-hydroxylase human Factor Inhibiting HIF (FIH) is an important regulator of the transcriptional activity of hypoxia inducible factor (HIF). FIH also catalyses the hydroxylation of asparaginyl and other residues in ankyrin repeat domain (ARD) containing proteins, including apoptosis stimulating of p53 protein (ASPP) family members. ASPP2 is reported to undergo a single FIH catalysed hydroxylation at Asn-986. We report biochemical and crystallographic evidence showing FIH catalyses the unprecedented post-translational hydroxylation of both asparaginyl-residues in "VNVN" and related motifs of ankyrin repeat domains in ASPP proteins (i.e. ASPP1, ASPP2 and iASPP) and the related ASB11 and p18-INK4C proteins. Our biochemical results extend the substrate scope of FIH catalysis and may have implications for its biological roles, including in the hypoxic response and ASPP family function.